The involvement of TLR2 and TLR4 in cytokine and nitric oxide production in visceral leishmaniasis patients before and after treatment with anti-leishmanial drugs - Gatto, Mariana [UNESP]; Abreu, Mariana Miziara de [UNESP]; Tasca, Karen Ingrid [UNESP]; Golim, Marjorie de Assis [UNESP]; Mendes da Silva, Laura Denise [UNESP]; Simao, Jose Cludio; Castelo Branco Fortaleza, Carlos Magno [UNESP]; Victoriano de Campos Soares, Angela Maria [UNESP]; Calvi, Sueli Aparecida [UNESP] (Public Library Science, 2015)
Toll-like receptors (TLRs) have significant involvement in Leishmania infection, although little is known about the relationship between these receptors, cytokines and nitric oxide (NO) in patients with visceral leishmaniasis (VL) before or after treatment with anti-leishmanial drugs. The goal of this study was to evaluate the expression of TLR2 and TLR4 in CD3(+) and CD14(+) cells and the production of TNF-alpha, IFN-gamma, IL-17, IL-10, TGF-beta and NO in peripheral blood mononuclear cells (PBMCs) from VL patients pre- and post-treatment with anti-leishmanial drugs. In addition, we investigated whether these receptors were involved in the production of these cytokines and NO. In the active VL patients, increased TLR2 and TLR4 expression in lymphocytes and monocytes, increased production of TNF-alpha, IL-10 and TGF-beta and decreased production of IFN-gamma, IL-17 and NO were observed. After treatment, TLR2 and TLR4 were still expressed in lymphocytes and monocytes, the TNF-alpha and IL-10 levels were lower, the production of IFN-gamma, IL-17 and NO was higher, and the TGF-beta level remained high. Before treatment, the production of TNF-alpha and NO was associated with TLR2 and TLR4 expression, while IL-10 production was only associated with TLR2 expression. After treatment, both receptors were associated with the production of TNF-alpha, IFN-gamma, IL-10 and NO, while the production of IL-17 was associated only with TLR4 expression. The results presented in this study suggest that both TLR2 and TLR4 participate in the modulation of cytokine and NO production in VL patients, contributing to the pathogenesis of VL prior to treatment and the protective immune response after treatment.